2020
DOI: 10.1021/acs.iecr.0c03112
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cs-Ru/CeO2 Spherical Catalyst Prepared by Impregnation and Washing Processes for Low-Temperature Decomposition of NH3: Characterization and Kinetic Analysis Results

Abstract: Cl-free Ru/CeO 2 spherical catalysts were prepared by incipient wetness impregnation and subsequent washing processes using RuCl 3 •3H 2 O and a commercial spherical CeO 2 support. Cs addition improved the catalytic performance for NH 3 decomposition, and the optimal Cs loading was a Cs/Ru molar ratio of 0.43. Transmission electron microscopy (TEM) and scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM−EDX) suggested that Cs was present around Ru metal particles and served as an anchor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…In addition to the active metal, the support also played an important role in the performance of the catalyst. The noble metal catalyst Ru showed different performances on CeO 2 , 75 Al 2 O 3 , 76 and MgO supports. 77 Vaninice et al found that at 683 K, the ammonia decomposition performance of 1.6% Ru/ Al 2 O 3 catalyst was one order of magnitude higher than that of 4.8% Ru/C catalyst, but there was no significant difference in the activation energy.…”
Section: Support Optimizationmentioning
confidence: 97%
“…In addition to the active metal, the support also played an important role in the performance of the catalyst. The noble metal catalyst Ru showed different performances on CeO 2 , 75 Al 2 O 3 , 76 and MgO supports. 77 Vaninice et al found that at 683 K, the ammonia decomposition performance of 1.6% Ru/ Al 2 O 3 catalyst was one order of magnitude higher than that of 4.8% Ru/C catalyst, but there was no significant difference in the activation energy.…”
Section: Support Optimizationmentioning
confidence: 97%
“…They demonstrated the main factor leading to the difference that the catalyst synthesized by the NaBH 4 reduction process was free of chloride, while the catalyst synthesized by the WI process contained more than 5 wt % Cl. Besides, Ru/CeO 2 spherical catalysts free of Cl were also synthesized by the WI process and subsequent washing processes . In addition to the mentioned drawbacks, the wet impregnation method is still extensively employed as an easy procedure to carry out research on ruthenium-based catalysts …”
Section: Ammonia Decomposition Hydrogen Production Catalystmentioning
confidence: 99%
“…It was just these Cs-promoted active Ru nanoparticles that promoted the recombination desorption of nitrogen atoms, which may be the rate-limiting step of the catalytic reaction. Furusawa et al 57 prepared Cl-free Ru/CeO 2 catalysts and reported that the doping of Cs efficiently enhanced the catalytic activity in NH 3 decomposition. They demonstrated that the optimal molar ratio of Cs/Ru is 0.43, and in ammonia decomposition reaction, Cs acted as an anchor for the production of small and widely distributed ruthenium nanoparticles (∼2 nm).…”
Section: Energymentioning
confidence: 99%
“…This showed that the positive benefits from the removal of chloride are significant and can even be stronger than the negative benefits from the increase in the ruthenium particle size. In addition, the use of reductants such as NaBH 4 , hydrazine, , and ammonia also could remove Cl from the catalyst surface during the preparation process. Therefore, in many reports involving Ru-based catalysts that may have chloride ions, the removal of chloride ions from the catalysts is also necessary and important. , …”
Section: Noble Metalsmentioning
confidence: 99%
“…K. Hill et al 57 added Cs as an electron promoter to Ru/ CNTs and observed the existence of an optimum Cs/Ru ratio at which the catalyst showed a significant increase in catalytic activity (turnover frequency (TOF) increased from 6.5 mol NH3 / (mol Ru •h) to 154.4 mol NH3 /(mol Ru •h), at 600 K) and a significant decrease in activation energy (from 96.7 to 59.3 kJ/ mol) due to the excellent electronic modification ability of cesium. T. Furusawa et al 36 also doped the Ru/CeO 2 catalyst with Cs as promoter. The addition of Cs effectively prevented the aggregation of Ru metal particles during high-temperature pretreatment, keeping a small particle size and high dispersion of Ru particles.…”
Section: Noble Metalsmentioning
confidence: 99%